Hubungan antara Pemberian Remdesivir dan Durasi Rawat Inap Dibandingkan Favipiravir pada Pasien Covid-19 - Alhilal Hamdi M.Nur; Heni Muflihah; Uci Ary Lantika (UNISBA Press, 2022)
Abstarct. One of the pharmacological treatments for COVID-19 recommended by the World Health Organization (WHO) is remdesivir. Based on the Indonesian COVID-19 management manual, among the antivirals used are remdesivir and favipiravir. Remdesivir is indicated for severe patients, while favipiravir is indicated for moderate to severe patients. The selection of remdesivir or favipiravir based on clinical characteristics and benefits in COVID-19 patients in Indonesia has not been widely carried out. The benefits of pharmacological therapy in hospitalized COVID-19 patients can be seen, one of which is based on the duration of hospitalization. This study aimed to analyze the relationship between remdesivir use and duration of hospitalization compared to favipiravir in hospitalized COVID-19 patients. This study is a retrospective observational analytic study using medical record data. The subjects of this study were hospitalized COVID-19 patients at Al-Ihsan Hospital for the period December 2020 to March 2021. The data studied included clinical characteristics, oxygen saturation (SpO2), administration of remdesivir or favipiravir therapy, and duration of hospitalization. The subjects of this study were 102 people, consisting of 51 people in the remdesivir group and 51 people in the favipiravir group. Remdesivir is mostly given to patients aged > 50 years (72.5%) while favipiravir is mostly used in patients aged 18-50 years (53%). Severe grade patients (SpO2 <90%) had a median duration of hospitalization of 11 days, while non-severe patients (SpO2 >90%) had a median of 9 days. The remdesivir group had a median duration of hospital stay of 10 days while that of favipiravir was 11 days. Statistically there was no association between remdesivir administration and duration of hospitalization compared to favipiravir in COVID-19 patients (p-value = 0.2436). Remdesivir did not provide a clinical improvement in the duration of hospital stay when compared with favipiravir. Abstrak. Salah satu tatalaksana farmakologi COVID-19 yang dianjurkan World Health Organization (WHO) adalah remdesivir. Berdasarkan buku pedoman tatalaksana COVID-19 Indonesia, diantara antivirus yang digunakan adalah remdesivir dan favipiravir. Remdesivir diindikasikan untuk pasien derajat berat, sedangkan favipiravir untuk pasien derajat tidak berat sampai berat. Pemilihan jenis antivirus remdesivir atau favipiravir berdasarkan karakteristik klinis dan manfaatnya pada pasien COVID-19 di Indonesia belum banyak dilakukan. Manfaat terapi farmakologi pada pasien COVID-19 rawat inap dapat dilihat salah satunya berdasarkan durasi rawat inap. Penelitian ini bertujuan untuk menganalisis hubungan penggunaan remdesivir dan durasi rawat inap dibandingkan favipiravir pada pasien COVID-19 rawat inap. Penelitian ini merupakan penelitian analitik observasional retrospective menggunakan data rekam medik. Subyek penelitian ini adalah pasien COVID-19 rawat inap di RSUD Al-Ihsan periode Desember 2020 sampai Maret 2021. Data yang diteliti meliputi karakteristik klinis, saturasi oksigen (SpO2), pemberian terapi remdesivir atau favipiravir, dan durasi rawat inap. Subyek penelitian ini berjumlah 102 orang yang terdiri dari 51 orang kelompok terapi remdesivir dan 51 orang kelompok favipiravir. Remdesivir banyak diberikan pada pasien berusia > 50tahun (72.5%) sedangkan favipiravir banyak digunakan pada usia 18-50 tahun (53%). Pasien derajat berat (SpO2 <90%) memiliki durasi rawat inap dengan median 11 hari sedangkan pasien derajat tidak berat (SpO2 >90%) memiliki median 9 hari. Kelompok terapi remdesivir memiliki median durasi rawat inap 10 hari sedangkan favipiravir 11 hari. Secara statistik tidak terdapat hubungan antara pemberian obat remdesivir dan durasi rawat inap dibandingkan favipiravir pada pasien COVID-19 (p-value = 0.2436). Remdesivir tidak memberikan perbaikan klinis durasi raawat inap jika dibandingkan dengan favipiravir.